PENGARUH KUALITAS PELAYANAN, KETEPATAN WAKTU DAN FASILITAS TERHADAP KEPUASAN PELANGGAN PT KARUNIA INDAH DELAPAN EXPRESS (PT KI8) CABANG SOLO - Maharani, Septiana; Sulistyowati, Pemilia; Rasminto, Hendri; Sati, Dian Laras (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
The population in this study were PT.KI8 service users. The sample size was 96 respondents. Data collection was carried out through distributing questionnaires, this researcher measured using a Likert scale with answers that had a gradation of very positive to very negative, the data collected would be processed using computational calculations from the SPSS program. This research aims to determine the influence of service quality,timeliness of delivery and facilities simultaneously on customer satisfaction at PT.KI8 Solo Branch using quantitative research. The variables of this research are Service Quality (X1), Timeliness of Delivery (X2) and Facilities (X2), on Customer Satisfaction (Y). The influence test method used is a statistical analysis method consisting of multiple linear regression tests, namely determination analysis, significant testing, hypotheses consisting of the T test and F test. Based on the results of the analysis, it can be concluded that (1) the service quality variable has no significant effect on customer satisfaction ( 2) the on-time variable has a significant effect on customer satisfaction (3) the facility variable has a significant effect on customer satisfaction (4) service quality, timeliness and facilities together have a significant effect on customer satisfaction.